Similarities in the Low-Energy Elastic and Ps Formation Differential Cross-Sections for e+-H and e+-He Scattering - Peter Van Reeth; John W. Humberston (Atoms, 2025)
Scattering differential cross-sections (DCSs) are important tools, both experimentally and theoretically, in the investigation of scattering processes in lepton–atom collisions. In the present work, the elastic scattering differential cross-sections (EDCSs) for e+-H and e+-He below the first excitation threshold of the target were evaluated using the Kohn variational method and found to be very similar. In both cases, the EDCS below the positronium formation threshold, i.e., for pure elastic scattering, had minimum valley features in which significant minima close to 90 degrees were found at ≈2.8 eV for H and ≈2 eV for He. These minima were shown to be linked to the zero in the s-wave phase shift, which gives rise to the Ramsauer minimum in the elastic integrated cross-sections. They were not vortices, but the overall EDCS structure was found to be related to the structures and vortices found in the Ps formation differential cross-sections just above the Ps formation threshold. The valley-type structure in the EDCS went smoothly through the Ps formation threshold, where it linked up with a similar valley structure in both the EDCS above the threshold and the Ps formation DCS. A comparison with the EDCS for e−-H and e−-He scattering over the same energy range revealed similarities with the positron EDCS, however, with less pronounced structures that had different angular and momentum dependences.